Ketogenic diet and intermittent fasting - impact on body weight and various diseases - Kuźniar, Julia; Kozubek, Patrycja; Czaja, Magdalena; Sitka, Hanna; Wegenko, Cezary (Journal of Education, Health and Sport, 2024)
Introduction and purpose: Obesity affects every age group and is associated with many negative health effects. Various diets are used to remove excess body weight. Recently, popular became two diets - intermittent fasting and ketogenic diet. Material and Method: This paper reviews various types of research documents published since 2018. Its main aim is to summarize the latest knowledge of ketogenic diet and intermittent fasting, including contraindications, side effects, impact on body weight and many diseases. It is also aimed to highlight the need for future research of the effects of both diets on various diseases and body weight reduction. Results: Both diets may be effective in weight loss and show other health benefits. Both ketogenic diet and intermittent fasting have proven to be effective in weight reduction. In the case of intermittent fasting the biggest impact on weight loss is calorie restriction. Ketogenic diet is effective as a result of calorie restriction, increased gluconeogenesis and loss of free water through increased diuresis. They can be used in the prevention and treatment of many diseases, including cardiovascular disorders, neurological disorders or potentially cancer. However, they cannot be administered by everyone and may cause dangerous side effects. Conclusion: Ketogenic diet and intermittent fasting are successful strategies for body weight reduction. Moreover, both of them may be used as an additional therapy for various diseases. However, patients should be under supervision.